Implementasi Sensor Cahaya dan Regulator Switching Buck Boost Sebagai Pengatur Tegangan Lampu untuk Meningkatkan Efesiensi Kelitrikan Honda Revo - Adit Nugraha; Medi Yuwono Tharam (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
The motorcycle lighting system often experiences voltage fluctuations due to changes in engine speed and electrical load, which can reduce LED lamp performance and lifespan. This study designs and implements a voltage monitoring and protection system for the Honda Revo using an ESP32 microcontroller, a buck-boost switching regulator, and an LDR sensor. The system monitors voltage in real time and stabilizes the lamp output at 12 V, while automatically disconnecting the power when voltage exceeds 13 V. The LDR sensor adjusts lamp brightness based on ambient light intensity to improve efficiency. Testing shows the rectifier output ranges from 13.2 V to 14.4 V during operation. The buck-boost converter successfully maintains a stable 12 V output despite input fluctuations. Overall, the system effectively enhances voltage stability, safety, and electrical efficiency, while supporting longer LED lamp lifetime.